MEAT-LARD PRODUCTION AND PHYSICAL AND CHEMICAL PROPERTIES OF PORK OF DIFFERENT PIG GENOTYPES - Баранова, Г. В. (Scientific Progress & Innovations, 2014)
The article is devoted to the comparative study of feeding and meat qualities of sows that belong to different productivity lines: Large White (universal) breed, Landras breed and cross-breed sows in the similar conditions of feeding and keeping. Productivity has been defined based on the feeding, slaughter and carcass traits of young animals of different genotypes during growing and control fattening period. The results of the research prove that sow productive qualities are positively conditioned by the genotype. The best breed combinations of sows that provide heterosis effect in productive qualities have been experimentally determined. Sows of cross-breed genotypes proved to excel the analogous sows of Large White and Landras breed in most productivity indices.